Determining the Lexical Minimum in Teaching the Russian Language to the Students of Agrarian Higher Education Institutions - Burkhanova Guzal Mukhammadievna (Zien Journals, 2024)
The article is focused on the methodology of improving the lexical competence of future specialists of agricultural higher educational institutions, and the issues of determining the lexical minimum of the specialized specialty are analyzed. Although the content of teaching the Russian language and its structure have been thoroughly researched, it has not yet been researched which of them are necessary and necessary for the formation of lexical competence. In the research work, the existing teaching content was analyzed, and it was aimed to determine the special content by introducing new additions.
Keywords: lexical competence; specialized education; selection; principle